The Effectiveness of the Interaction and Trust on the Intelligent Digital Assistants Usage - Almirabi, Alaa (2018)
The growing volume of data and the need to access information instantly has guided people to use technology. Intelligent Digital Assistant (IDA) developed as a sufficient tool to cover the web search engine features and more to meet the users’ dynamic needs. The IDA can be simply defined as a software that functions as a personal information manager such as Siri and Google Now. This is an explorative study that aims to identify the various factors that impact the usage of the IDA from two aspects which are interaction and trust regarding the future usage, in order to find out the most effective directions of development for the IDAs. The importance of this study is due to the increased numbers of the IDAs’ usage users. As mentioned by Gautier and Pestanes (2016), the usage time of these systems is converging to be one billion hours per month. The findings indicate that interaction and trust significantly and positively affect the IDA usage. The results show that ease of use and the less effort are positively associated with the IDAs adoption. However, giving an inappropriate answer or out of context dialogue affect the usage significantly but negatively. Therefore, quality and recognition accuracy are factors that should be developed to increase the rate of IDA’s usage.